Comportamiento de la mutación mtDNA A3243G en dos familias antioqueñas de pacientes diagnosticados con el síndrome MELAS (2010)
ABSTRACT: Mitochondrial DNA mutations cause mitochondrial cytopathies. Among them Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes (MELA) is the commonest. The transition 3243A>G in the Leucine tRNA is present in 80% of the patients. Heteroplasmy is observed in mitochondrial cytopathies, characterized by the coexistence of mutant and wild type molecules in a cell. Depending on the level of heteroplasmy, function and clinical manifestations might result affected. Objective: To test the degree of heteroplasmy of the mutation 3243G on its expression (syntoms) and nuclear-variants dependence. Patients and methods: Mutations in the tRNALeu gene were sought in 34 patients by sequencing and PCR-RFLP. Four SPA (specific population alleles) were typed in patients and their relatives carrying the mutation 3243A>G. Results: The mutation 3243A>G in the Leucine tRNA gene was found in two patients. This mutation was screened in their relatives and the amount of mutant DNA (MDNA) was assessed. The index cases presented with the higher amounts of MDNA in both families. In family one, the mutation was detected in 14 members, three of which presented with short stature, one with hearing loss, one with type 2 diabetes, 8 with migraine and one healthy individual. In family two the mutation was detected in one member with brain paralysis, two with migraine and one healthy individual. Conclusions: Severity of the symptoms in patients affected with MELAS is correlated with the amount of MDNA. Furthermore, it was found a correlation between MDNA and IAA, suggesting a possible effect of amerind nuclear ontext in The mitochondrial segregation and replication.